Values of the ukrainian society and state vs the values acquired during european integration - Mishyna, N. V. (НТУ ДП, 2022)
Ukraine's European integration is accelerating, as evidenced by the active work of public authorities - both national and local. In this regard, an important scientific and practical task is to monitor how society perceives this movement. When it comes to the European integration, most of the population of Ukraine, according to statistics, supports it - in general. However, the process of preparation for accession to the European Union requires more weighty social advertising - both in the number of issues it would cover and in the intensity of the advertising campaign. It would be expedient to develop an appropriate concept at the national level (for example, this could be entrusted to the Cabinet of Ministers of Ukraine). This is an important factor in the further formation and strengthening of constitutional legal awareness, constitutional culture.

Європейська інтеграція України прискорюється, про що свідчить активна діяльність в органи державної влади – як національні, так і місцеві. У зв'язку з цим важливе науково-практ Завдання полягає в тому, щоб відстежити, як суспільство сприймає цей рух. Коли йдеться про євроінтеграцію, більшість населення України, за статистикою підтримує його - загалом. Проте процес підготовки до вступу в Європейський Союз вимагає більш вагома соціальна реклама – як за кількістю питань, які вона висвітлюватиме, так і за інтенсивність рекламної кампанії. Було б доцільно розробити відповідний концепції на національному рівні (наприклад, це можна було б доручити Кабінету Міністрів). України). Це важливий фактор подальшого формування та зміцнення конституційна правосвідомість, конституційна культура.
Keywords: суспільство; держава; євроінтеграція; органи державної влади; Європейський союз